"Organic" Gift-Giving and Organ Transplantation, the Development of Economic Sociology and Morality in a Super-Monetized World: An Interview with Philippe Steiner - Steiner, Philippe (Экономическая социология, 2014)
Philippe Steiner, Professor of Sociology at Paris-Sorbonne University, was interviewed by Chris Swader, Associate Professor of Sociology at the Higher School of Economics. This interview was conducted during the international conference “Embeddedness and Beyond: Do Sociological Theories Meet Economic Realities?” (Moscow, 25–28October 2012), at which Prof. Steiner co-chaired the mini-conference “Market Society and Moral Order”. In the interview, Prof. Steiner described his background and the professional trajectory that led him to economic sociology. He explained how his research interests in organ donation and transplantation developed. Prof. Steiner devoted several comments to plans for future research. He was primarily interested in two topics: (a) organizational gift-giving and (b) how gift-giving and markets co-exist in the same spaces. Additionally, Prof. Steiner depicted the process of institutionalization of economic sociology as an academic discipline in France and noted several peculiarities of French economic sociology compared with the US and Brazilian versions. Finally, Prof. Steiner discussed the Polanyian perspective and Zelizer’s research and clarified his own view of the super-monetization of the modern world. According to Steiner, Zelizer’s fascinating depiction of a world dominated by commodification and money may have evaded political issues that were central to Polanyi and decisive for understanding contemporary markets.